APPROXIMATION METHOD FOR A MULTILAYER TRANSVERSELY ISOTROPIC MATERIAL - Писаренко, Олександр (SWorldJournal, 2025)
This study analyzes in detail the advantages of using an approximation method to describe the propagation of Lamb wave packets in multilayer structures using laminated composites as an example. It is shown that the approximation technique for a multilayer